Crisis informatics in smart campus: opportunities, challenges, and future directions - Bukar, Umar Ali; A. Jabar, Marzanah; Sidi, Fatimah (Database Technologies and Applications Research Group (DbTA), Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2019)
Crisis Informatics is a term that describes the use of social media for emergency. This paper select articles on schools crisis communication from an ongoing research on assessment of crisis communication theories and models. The focus is to present state of the art opportunities and challenges facing universities and educational establishment in crisis. This review helps stakeholders to see the significance of social media as part of the crisis communication plan. The findings recommend ways for future research and for emergency correspondence to comprehend the significance of the universities utilization of social media during an emergency, why that is significant, and why specialists should make viable social media communication strategies a need during an emergency.